Changing Craft in the Early Renaissance. Florentine Citizens and the Profession of Arms (1427–1430) - Picchianti, Simone (Faces of War, 2024)
Between the end of the 14th century and the beginning of the 15th century, the Republic of Florence was almost constantly engaged in war. As a result, public debt in a short time increased from 1 million to 3 million florins. The most difficult time for the Republic occurred between the years 1425 and 1433. In this phase, authorities experimented with new forms of taxation to cope with the growing expenses, including the cadaster (Catasto) created in 1427, pursuant to which Florentine citizens were forced to list all their assets in addition to other personal information. Based on the information provided by this document, it has been possible to identify all Florentine citizens who were soldiers at the time. Furthermore, thanks to the data extracted from the accounting records of the Florentine government of 1430, it has been possible to evaluate an interesting change in society: several artisans, of various ages, abandoned their professions to become soldiers. According to the documents, such a choice was seen as a chance to one’s economic condition thanks to the considerable wages and good working conditions offered by the Republic compared to those associated with work as artisans.